Developing AI Regulations in Indonesia: Policy Recommendations Based on Comparative Policy Analysis from the European Union, the United States, and Singapore - Revolusi, Prabu; Febriandy, Radians Krisna (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
Artificial intelligence (AI) is increasingly becoming the main driver of digital transformation in various sectors such as education, health, and finance. However, this development raises regulatory challenges, particularly regarding privacy protection, algorithm transparency, and AI usage ethics. Indonesia, with a high level of technology adoption but without a specific legal framework, faces the risk of misuse of this technology. This study uses a literature review and a comparative policy analysis approach to examine AI regulations in the European Union, the United States, and Singapore. The results of the analysis show that the European Union emphasizes data protection and strict supervision, the United States promotes flexibility for innovation, while Singapore offers a balance between social responsibility and technological progress. Based on these findings, this article recommends developing an AI regulatory framework in Indonesia by combining the principles of a risk-based approach, transparency, and algorithmic auditing, as well as the establishment of an independent AI regulatory agency. This regulation is expected to encourage innovation that is safe, ethical, and adaptive to technological dynamics.